The external controller solutions (ECS) based on programmable logic controller with humanmachine interface: A case study for the water level simulator plant - Patrialova, Sefi Novendra; Winata, Waga; Mujiyanti, Safira Firdaus; Adziima, Ahmad Fauzan; Wahyu Nugroho, Dwi Oktavianto (Faculty of Vocational Studies - Research Center, DRPM ITS, 2024)
The External Controller Solutions (ECS) is designed with the flexibility and able to be integrated with various plants. The ECS has been built using PLC and HMI. Several tests have been carried out in developing this ECS, including testing Digital Input/Output (DI/DO) and Analog Input/Output (AI/AO) voltages. This ECS be able to control up-to 8 devices simultaneously with the data refresh time interval of 100 ms and be able to handle up-to 10,000 operating cycles within 24 hours without significant performance degradation. ECS performance is very good, proven by the results showing that the system runs well within 20-35 °C of temperatures range and 20%-80% of humidity. To show the advantage of ECS, it has already been integrated on the Water Level Simulator (WLS) plant and successfully controlled the flow through the VSD at 54 RPM/Hz in range of 15-30 Hz.